PEMETAAN POTENSI PRODUKSI PADI SAWAH (Oryza sativa L.) DI KAWASAN DUMOGA KABUPATEN BOLAANG MONGONDOW DENGAN MENGGUNAKAN MODEL SIMULASI TANAMAN - Romy Kanakan; Johanes E.X. Rogi; Paula C.H. Supit (Universitas Sam Ratulangi, 2017)
ABSTRACT Dumoga area Bolaang Mongondow Regency is a region mainstay for production center largest rice fields Bolaang Mongondow Regency North Sulawesi Province, because having the condition agroklimat suitable for growth of paddy fields. To know growth and development paddy fields in the region Dumoga Bolaang Mongondow Regency with varying conditions agroklimat can use the model simulated plants. This study attempts to determine the potential production of rice fields in the region Dumoga Bolaang Mongondow Regency using a model of paddy Shierary rice. This research be conducted in the Siniyung Village Subdistrict Dumoga, Modomang Village Subdistrict East Dumoga and Ikhwan Village Subdistrict West Dumoga Bolaang Mongondow Regency and Laboratory modeling and Ecosystems Agriculture Faculty of Sam Ratulangi University for the implementation of a simulated plants and Geographic Information System. The result show that potential production of rice fields in the Siniyung Village Subdistrict 6,53 ton ha1, Modomang Village Subdistrict East Dumoga 4,93 ton ha-1, and Ikhwan Village Subdistrict West Dumoga 4,83 ton ha-1. Production potential highest in the Siniyung Village namely 6,53 ton ha-1 caused having radiation high namely 22,79 MJ m-2 hari-1, rainfall 269,65 mm/month, and temperature 23,84 oC. Keywords: Rice, Potential Production